The last launch : messages in the bottle - Tuan, Yi-fu, 1930-2022 (Staunton, VA : George F. Thompson Publishing, L.L.C., 2015)
"The Last Launch is a treasure trove of personal visions of wisdom and faith that demonstrate the connections we all have with one another. Tuan's concluding section of 'favorites' alone holds abundant gems from a master scholar who now shares, for the last time in an illustrious career, a lifetime of erudition and teaching. Tuan's work welcomes readers to gather their own religious and ethical/philosophical foundations that can serve as building-blocks for their own faith and direction, especially in relation to the communities and larger world in which they live, learn, and grow. By entering Tuan's stories, young readers, especially, are challenged to become more aware of who they are and who they want to become." -- Dr. Katherine Low.
Prologue : closing the circle -- The personal and the geographical revisited -- Understanding social reality -- Seeking goodness and the good -- God, Christianity, and religious faith -- Messages to the young -- Reflections of the self.
Includes bibliographical references (pages 197-203).
Keywords: Tuan, Yi-fu, -- 1930-; Geographers -- United States -- Biography; College teachers -- States -- Bioraphy; Geography -- Philosophy